Medical First-Trimester Termination of Pregnancy with Massive Fibroid Uterus - Michael Saad-Naguib; Karla Maguire; Christine Curry; Usha Verma (Case Reports in Obstetrics and Gynecology)
First-trimester termination of pregnancy by medical or surgical route is highly effective with a low complication rate. Uterine abnormalities can complicate a procedure due to distortion of normal anatomy. In this case presentation, medical termination of pregnancy is performed using fetal intracardiac potassium chloride injection and intramuscular methotrexate.